MicroRNA expression in chronic lymphocytic leukemia developing autoimmune hemolytic anemia. Issue 9 (September 2013) - Ferrer, Gerardo; Navarro, Alfons; Hodgson, Kate; Aymerich, Marta; Pereira, Arturo; Baumann, Tycho; Monzo, Mariano; Moreno, Carol; Montserrat, Emili
Abstract: Chronic lymphocytic leukemia (CLL) is frequently associated with autoimmune hemolytic anemia (AIHA). However, the mechanisms governing the association between CLL and AIHA are poorly understood. MicroRNAs (miRNAs) have been associated with different clinico-biological forms of CLL and are also known to play a substantial role in autoimmunity. However, there are no studies correlating miRNA expression with the likelihood that patients with CLL will develop AIHA. In this study, we found that malignant B-cells from patients with CLL subsequently developing AIHA present nine down-regulated (i.e. miR-19a, miR-20a, miR-29c, miR-146b-5p, miR-186, miR-223, miR-324-3p, miR-484 and miR-660) miRNAs. Interestingly, two of these miRNAs (i.e. miR-20a and miR-146b-5p) are involved in autoimmune phenomena, and one (i.e. miR-146b-5p) in both autoimmunity and CLL. Furthermore, we demonstrated that miR-146b-5p modulates CD80, a molecule associated with the B–T-cell synapse and in restoration of the antigen presenting cell capacity of CLL cells.